Hand grip strength as an indicator of Bone Mineral Density and hand function in preschool children - Hasan, Noha Abdel KaderAbdel Kader; Eltalawy, Hoda A; El-Banna, Rokia A (International Journal of Psychosocial Rehabilitation, 2020)
Hand grip strength is one of the best indicators of the overall strength of the upper limb and it is evaluated as a component of hand function upper limbs play an important role in subject’s daily life.use of HGS is a single, simple and inexpensive method for assessing general muscle strength, function and bone health in children which is important to identify children who may be at risk of poor mineral accretion or future risk of osteoporosis due to low bone mineral densitypurposeof this studyTo investigate correlation between bone mineral density with both hand grip strength and hand function in preschool children and to search about cheap, valid indicator of bone density in children. Subjects and Methods: Sixty normal preschool children, with age ranging from 4 to 6 years old both sexes participated in this study, children were selected from nurseries and charitable orphanages at urban region of Cairo Governorate; namely (Awladi).Each child was evaluated individually byusing Peabody Developmental Motor Scale (PDMS-2) to determine standard scores of visual-motor integration subtestand age equivalent for fine motor activities and Baseline pneumatic squeeze handheld dynamometer todetect maximum hand grip strength, Bone mineral density was assessed by DEXA at National Research Center for all children Results:The results of this study revealed significant correlation between hand grip strength with bone mineral density and hand function Conclusion: hand grip strength could be used as a predictor for bone density and hand skill in preschool children